Effect of Maize (Zea mays) on Thyroid Status under Conditions of Varying Iodine Intake in Rats - Chandra, Amar K.; Ghosh, Dishari (Journal of Endocrinology and Reproduction, 2009)
Maize (Zea mays) is the third most planted food crop and one of the major energy sources among the people of the semiarid tropics. Presence of cyanogenic glucosides, which are antithyroidal substances, in maize is well established. However, the effect of chronic consumption of maize on thyroid status under varying levels of iodine nutrition remains unexplored. In this study, goitrogenic content and in vitro thyroid peroxidase (TPO) inhibiting activity of maize of Indian origin, along with its in vivo anti-thyroid potential without and with extra iodine supplementation, has been evaluated. Edible part of maize contains thiocyanate (20 ± 2mg/kg), cyanogenic glucosides (10.12 ± 1.2 mg/kg) and glucosinolates (2.5 ± 0.2 mg/kg). In vitro inhibition of TPO activity was found in fresh maize extract but the presence of extra iodide in the incubation media showed reduction in such inhibition to a certain extent. Inhibition constant (IC50) and PTU equivalence of fresh maize were 66.25 ± 1.42 Î¼g and 1.36, respectively. Significant increase in urinary excretion of thiocyanate and iodine was observed in the rats fed maize for 45 days and 90 days, respectively, associated with increased thyroid weight, decreased TPO activity and serum total circulating T4 and T3 levels as compared to their respective controls. A relative state of morphological as well as biochemical hypothyroidism developed gradually in chronic maize fed rats. Adequate iodine supplementation in maize fed groups of rats improved the thyroid status to a certain extent but failed to prevent the antithyroidal activity of the plant food.